IMPLEMENTASI MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA KELAS IV SEKOLAH DASAR - Alfadila, Ufara; Muhisom; Kembar Habibi, Roy; Syafrudin, Ulwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the suboptimal learning outcomes of students based on the learning objective achievement criteria in the Pancasila Education subject at SD Negeri 2 Kota Gajah. This study aimed to determine the effect of implementing the cooperative learning model of the Teams Games Tournament type on the learning outcomes of fourth-grade students in Pancasila Education at SD Negeri 2 Kota Gajah. This research employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The sample consisted of 53 students who were divided into an experimental class and a control class. Data were collected through test and non-test techniques. Data analysis using simple linear regression revealed a significance value of 0.000 < 0.05, indicating that the implementation of the Teams Games Tournament cooperative learning model had a significant effect on the Pancasila Education learning outcomes of fourth-grade students at SD Negeri 2 Kota Gajah.